Documentation of accidental, casual, and regular species sightings compiled by Thomas H. Kent, spring 1983 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1983)
A report of documented sightings of accidental, casual, and regular species compiled by Thomas H. Kent. There were 90 documentations, 65 birds and 39 species in total. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed/flatbed